Identifying Code Hero In Ernest Hemingway’s A Farewell To Arms and The Sun Also Rises - Goughari, Athareh Shahsavari (2010)
This research looks at Ernest Hemingway's A Farewell to Arms and The Sun Also Rises in order to explore the specific characteristics found in Hemingway's code hero as these heroes share certain attitudes and characteristics found in all Hemingway's novels. This project wants to illustrate the Phillip Young's concept of code hero in Hemingway's selected novels as he is the first scholar who has created characteristics Hemingway's code hero for the first time. He has named these heroes "code hero" due to certain characteristics such as sense of nothingness, grace under pressure, courage and dignity that recur through all these code heroes. By introducing this type of hero, Hemingway has added a new branch to the theory of heroism. By using heroism theory this project wants to illustrate the fundamental similarities and differences of this new type of hero with other definitions in heroism theory. This research will next examine the complexities and integrities found in Hemingway's code hero. Due to direct relationship between Hemingway's background and his code heroes, this thesis also discusses how Hemingway tries to foreshadow his own life and moralities in his code heroes and will relate the creation of this certain hero to the characteristics of Hemingway's spiritual life. This research also examines how Hemingway throughout depiction of his code hero and especially with the description of nada conception highlights the pessimistic view of the code hero and shows the position of early modern man in civilized society.